Reply to 'Lifshitz-point critical behaviour to O(epsilon(2)(L))' - de Albuquerque, L. C.; Leite, M. M. (Iop Publishing Ltd, 2002)
We reply to a recent comment by Diehl and Shpot (2001 J. Phys. A: Math. Gen. 34 9101) criticizing our paper (Albuquerque L C and Leite M M 2001 J. Phys. A: Math. Gen. 34 L327). We show that the approximation we use for evaluating higher loop integrals is consistent with homogeneity. A new renormalization group approach is presented in order to compare the two methods with high-precision numerical data concerning the uniaxial case. We stress that isotropic behaviour cannot be obtained from anisotropic behaviour.